PENGARUH BAHASA GAUL TERHADAP PENGGUNAAN BAHASA INDONESIA BAKU DI LINGKUNGAN SEKOLAH KELAS IV SD INPRES PARANG BERU KABUPATEN GOWA - Wafiq Asisah; Aco Karumpa; Rahmatiah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The main problem in this study is how the influence of Gaul language on the use of Indonesian language baku in the school environment of 4th grade SD Inpres Parang Beru district of Gowa. This research aims to know the impact of the language gaul on the usage of Indonesia baku language in school environment with the method of observation techniques, recording and documentation in the 4th class SD Inpress Parang beru. This type of research is descry ptive qualitative. Research procedures include data collection, data reduction, data presentation, verification and conclusion drawings. The subjects of this research are students of class IV SD Inpres Parang Beru district of Gowa of 5 people. The results of the research show that the use of Gaul language among students in particular in SD Inpress Parang Beru district Gowa has become a common trend because it is always used in communication and interaction between fellow students especially that use of such language is intense when playing, joking and talking to each other.